Multimedia Network File Servers: Multi-Channel Delay Sensitive Data Retrieval - Gemmell, Jim; Han, Jiawei (Association for Computing Machinery, Inc., 1994)
Delay sensitive media such as audio and video are becoming integrated in the standard user interface. In this paper we consider simultaneous multiple access, such as would be performed by a multimedia network file server. To simplify the discussion, we consider only audio retrieval. The extension to storage and other delay sensitive data types is straightforward. This paper builds on the necessity of avoiding starvation of the consumer, and the assumption that certain sets of reads lead to a net increase in the number of samples buffered, to establish a theoretical framework for studying simultaneous multiple access. Our approach allows the possibility of splitting data into sorting sets for the purpose of reducing disk latencies, and gives an optimal algorithm for the reduction. It explicitly handles both contiguous and non-contiguous file layouts. Lower bounds on read amounts and buffer requirements are proved. Using the theoretical framework, designers can evaluate the approach that is best suited to their situation.